Strategi Pembangunan Hutan Rakyat Pinus di Tana Toraja - Melewanto Patabang; Nurheni Wijayanto; H Hardjanto (Jurnal Manajemen Hutan Tropika, 2008)
The exploitation of pine people forest in Tana Toraja has just begun since pine wood manufacturing industry opened in 2002. In 2004, the activity of this manufacture was stopped as some local people protested the activity. They assumed that the exploitation and manufacturing would cause negative effect, as the stand value could be much higher than benefits of the industry. In 2006, Tana Toraja Regency Government allowed the exploitation of the pine tree and offered the investors who were interested to invest their capital in the exploitation. The exploitation certainly needed a strategy based on accurate and comprehensive data.  The aim of this research was to arrange a strategy of pine people forest exploitation which could give both economy and ecology benefits. This research used financial analysis, SWOT analysis, and Analytical Hierarchy Process.  The result of the analyses indicated that the strategy could be best applied was strength-threat (ST) by increasing the role of farmer organization, conducting agroforestry pattern development in order to increase land productivity, applying proper regulating area for planting and harvesting, and assuring the exploitation of tongkonan area.